Investigating the Prevalence of Urinary Incontinence among Women in Northern Afghanistan - Yaqubi, Abdul Ali; Hakimi, Abdul Qayum; Afzali, Qais (Journal for Research in Applied Sciences and Biotechnology, 2024)
Incontinence is a physical disability that is associated with social isolation and leads to anxiety, depression and reduced self-confidence. This disease is a common medical problem that may have adverse effects on their quality of life and social relationships. This descriptive-cross-sectional study was conducted in Mazar-e-Sharif in 1400-1401. The statistical population of this research consists of all women referring to Hakimi hospital. The samples included 100 women with the age of 40-60 years who had visited the hospital with various complaints including urinary incontinence. Sampling was simple random and 79 people were selected using Morgan's table. The data was collected with the help of a questionnaire and then entered into the SPSS 28 software for analysis. The findings show that among the (79) respondents, (39) respondents were between 40-50 years old, and (40) respondents were between 50-60 years old. (20) between the ages of 60-70 kg, (29) between 70-90 kg and (30) more than 90 kg. Among the patients, (12) had given birth 1-2 times, (28) had a normal birth and (34) had a non-normal birth (cesarean section). The average and standard deviation of the age of the participants was 80.5 ± 5.41 years, the average weight was 90.13 ± 12.98 kilograms, the average number of births was 4.23 ± 1.82, the average number of normal births was 3.42 ± 3.82, and the average number of non-normal or cesarean births was 29.16 ± 4.28. Urinary incontinence type was observed in (12) forte (15%), (44) combined (56%), (10) continuous (10%) and stress (13) tons (16%). The findings show that among the prevalence factors among patients, home birth (38%) and diabetes (25.4%) are among the most common causes of urinary incontinence among women. There was also a significant relationship between the use of contraceptives and incontinence. In the present study, there was a statistically significant relationship between age and suffering from administrative incontinence.